Influence of Leader’s Goal Setting, Inspirational, Motivational, and Intellectual Stimulation Behavior on Organizational Performance of Nepalese Engineering Colleges with Mediating Role of Monetary Reward - Gurung, Mahendra Bahadur; Kaur, Kamaljeet; Rahim, Hazrita Binti Ab.; Wagley, Thakur Prasad Sharma (Journal of Advanced Academic Research, 2026)
This paper examines how the leader’s transformational leadership behaviors such as goal setting, inspirational, motivational and intellectual stimulation, influence organizational performance and how one of the transactional leadership style – monetary reward – mediates the effect through senior level administrative staff and teaching faculty members as respondents at the engineering colleges setting in Nepal. By identifying the components of the transformational leadership practices, the study aims to improve academic environment and growth of the colleges as organizations. The calculated sample size using Slovin’s equation was 181, for which, 285 questionnaires were administered to all thirty engineering colleges operating in Kathmandu valley. The response questionnaires collected were 225, out of which 24 were screened out and the valid response questionnaires from 201 respondents were used for analysis. Stratified purposive random sampling was used for final survey in Nov. 2024-Jan, 2025, whereas stratified convenient random sampling was used for pilot survey in July 2024-Aug 2024. Reliability for pilot survey data was confirmed with Cronbach’s Alpha .965 and validity was ensured through past model questions, expert review and factor analysis. For the final survey data analysis, descriptive statistics, ANOVA and regression analyses were performed with PROCESS Macro in SPSS. The findings revealed that in the Nepalese context, all the four components of transformational leadership behavior have statistically positive and significant influence on the organizational performance of the engineering colleges showing the highest impact with regression coefficient .5844 for the first variable, ‘goal setting behavior’ for simple linear and .5471 also for the first variable for multiple linear regression models. For mediating effect of the variable monetary reward, however, the findings revealed mixed results showing statistically positive and significant effect for the second and the third variables, namely, ‘inspirational’ and ‘motivational’ variables and statistically positive but insignificant effect for the other two leadership styles, e.g., goal setting and intellectual stimulation. The study found that largely the influence of transformational leadership behavior on organizational performance was significant for the organizational improvement and growth. The findings and recommendations of the research may be generalized to the leaders of engineering colleges under all universities in the Nepalese context.